2018
DOI: 10.2174/1745017901814010323
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pediatric Epilepsy on Children and Families: A Multicenter Cross-Sectional Study

Abstract: Background and Objectives: Epilepsy is considered one of the most prevalent causes of morbidity in children. The aim of this study is to determine how epilepsy impacts the lives of children with epilepsy and their families. Methods: A translated version of the “Impact of Pediatric Epilepsy Scale” (IPES) questionnaire was completed by the 80 mothers of children with epilepsy, recruited at three hospitals in Jeddah, Sau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 61 publications
(66 reference statements)
0
7
1
Order By: Relevance
“…Some of those impacts are burden, stigma, deprivation from education, problems related to side effects of antiepileptic drugs, and poor QOL. QOL among parents of children with epilepsy was found to be lower as compared to parents of healthy children 5 . In children, epilepsy can be associated with developmental problems such as developmental delay, poor academic performance, inadequate social skills, and psychosocial problems such as attention‐deficit/hyperactivity disorders, intellectual disability, poor self‐esteem.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Some of those impacts are burden, stigma, deprivation from education, problems related to side effects of antiepileptic drugs, and poor QOL. QOL among parents of children with epilepsy was found to be lower as compared to parents of healthy children 5 . In children, epilepsy can be associated with developmental problems such as developmental delay, poor academic performance, inadequate social skills, and psychosocial problems such as attention‐deficit/hyperactivity disorders, intellectual disability, poor self‐esteem.…”
Section: Introductionmentioning
confidence: 89%
“…Many similar studies have been done in other countries of the world. As mentioned above, various studies have reported poor QOL among caregivers of patients with epilepsy 4‐8 . There is scantiness of literature regarding psychosocial aspects including QOL among caregivers of children living with epilepsy in Nepal where optimum resources are not available for managing childhood epilepsy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 11 ] Locally, a study was conducted in three hospitals in Jeddah to assess the impact of epilepsy on children. [ 12 ] The cause of seizure, monthly income, and child's nationality were significantly associated with QOL. Hypoxic-ischemic encephalopathy (HIE) and cerebral palsy (CP) were strongly linked with lower QOL.…”
Section: Introductionmentioning
confidence: 99%